Altered Dopamine Synaptic Markers in Postmortem Brain of Obese Subjects - Wu, Chun; Garamszegi, Susanna P.; Xie, Xiaobin; Mash, Deborah C. (Frontiers in human neuroscience, 2017)
Dopaminergic signaling in the reward pathway in the brain has been shown to play an important role in food intake and the development of obesity. Obese rats release less dopamine (DA) in the nucleus accumbens (NAc) after food intake, and amphetamine stimulated striatal DA release is reduced in obese subjects. These studies suggest that DA hypofunction associated with hedonic dysregulation is involved in the pathophysiology of obesity. To identify brain changes in obesity, quantitative measures of DA synaptic markers were compared in postmortem brain tissues of normal weight and obese subjects over a range of increasing body mass indices (BMI). DA transporter (DAT) numbers in the striatum were compared to the relative expression of DAT, tyrosine hydroxylase (TH) and D2 dopamine receptors (DRD2) in midbrain DA neurons. Radioligand binding assays of [ H]WIN35,428 demonstrated that the number of striatal DAT binding sites was inversely correlated with increasing BMI ( = -0.47; < 0.01). DAT and TH gene expression were significantly decreased in the somatodendritic compartment of obese subjects ( < 0.001), with no significant change in DRD2 compared to normal weight subjects. The reduced density of striatal DAT with corresponding reductions in DAT and TH gene expression in substantia nigra (SN) suggests, that obesity is associated with hypodopaminergic function. A DA reward deficiency syndrome has been suggested to underlie abnormal eating behavior that leads to obesity. Neurobiological changes in presynaptic DA markers demonstrated postmortem in human brain support a link between hedonic DA dysregulation and obesity.